(untitled) (Tạp chí Y học Cộng đồng, 2026)
Introduction: In the 21st century, Global Health (GH) has transitioned from a peripheral topic to a core component of medical education. However, in developing nations like Vietnam, the integration of GH curricula remains limited, and there is a paucity of data regarding students’ specific educational needs. This study explored the qualitative definitions of GH among Vietnamese health science students and their expectations for future curriculum development. Materials and Methods: A qualitative survey study utilizing open-ended questionnaires was conducted at the University of Medicine and Pharmacy at Ho Chi Minh City from June to July 2025. This article analyzes textual responses from a sample of 532 undergraduate students across six faculties. Data regarding students’ definitions of GH and recommendations for education were analyzed using Inductive Content Analysis to identify significant themes. Results: The analysis identified two primary themes. First, student conceptualizations of GH were predominantly disease-centric, reflecting a pandemic legacy, although a humanistic and ethical perspective also emerged. Second, there was a strong demand for pragmatic educational transformation, with specific requests to integrate GH into Case-Based Learning and utilize social media as an educational tool. Conclusion: Vietnamese health science students possess diverse but fragmented conceptualizations of GH, often conflating the field with disease control. Consequently, there is a critical need for a practical integration model in health professions education that shifts the focus from theory to clinical application and leverages digital platforms to meet learner expectations.